191 Clinical and Economic Outcomes of Patients Undergoing Surgical Intervention for Trigeminal Neuralgia: Analysis From a National Database. (1st April 2022) - Alexander, Yohan; Doherty, Ronan; Alvi, Mohammed A.; Yolcu, Yagiz; Kerezoudis, Panagiotis; Brown, Desmond A.; Agarwal, Vijay; Van Gompel, Jamie J.; Ghogawala, Zoher; Link, Michael J.; Meyer, Fredric B.
Abstract : INTRODUCTION: The management of trigeminal neuralgia (TN) has evolved significantly in the past century. In the current manuscript, we compare clinical and economic outcomes of patients undergoing surgical intervention for TN between microvascular decompression (MVD), percutaneous procedures and stereotactic radiosurgery (SRS) using a national database. METHODS: The national inpatient sample (NIS) was queried for cases undergoing a surgical intervention for TN between 2002-2015 3rd quarter using the International Classification of Disease 9th Revision Clinical Modification (ICD-9-CM) and procedure codes (ICD-9-PCS). Outcomes assessed included length of stay (LOS), discharge disposition and cost. RESULTS: A total of 8, 317 patients undergoing a surgical intervention for TN were identified between 2002 and 2015 3rd quarter, of which 7, 202 (86.6%) underwent MVD, 548 (6.6%) underwent percutaneous procedures and 567 (6.8%) underwent SRS. Patients undergoing percutaneous and SRS procedures were more likely to be older compared to those undergoing MVD (>65: 58.1% and 72.1% vs 32.2%, respectively; p < 0.001). MVD was significantly more likely to be performed in an urban academic institution compared to percutaneous procedures and SRS (84.8% vs 75.1% and 75.8%; p < 0.001). Patients undergoing SRS had the lowest LOS (1.34 days vs 3.2 days and 3.5 days; p < 0.001) and lowest odds for a prolonged LOS (OR = 0.29; CI: 0.18-0.46; p < 0.001) and non-routine discharge (OR = 0.44; CI: 0.28-0.71; p < 0.001). Percutaneous procedures had the highest odds for a prolonged LOS (OR = 2.07; CI: 1.65-2.61; p < 0.001). The total charges billed by the hospital were highest for patients undergoing MVD ($50, 432.30) followed by those undergoing SRS ($38, 450.90) and percutaneous procedures ($18, 655.10) (p < 0.001). The total reimbursed cost was highest for SRS ($18, 265.70) followed by MVD ($17, 590.20) and percutaneous procedures ($8, 183.30). CONCLUSION: In the current era of value-based care, these analyses are important in helping physicians, hospitals and other stakeholders devise appropriate policies to ensure optimal patient outcomes, as well as optimal reimbursements.